(untitled) (Nuntius Antiquus, 2022)
The impact of the social web on Classical Reception Studies has been vast and varied. This paper is a personal reflection on the influence of such tech-driven phenomena as mass digitization, database projects, social media, commercial web platforms and blogs on the thriving sub-discipline of classical reception. It discusses several online initiatives that have made their mark on the discipline, and also introduces some recent and future initiatives, which track methodological progress from the social (Web 2.0) to the semantic web (3.0).